Macrofaunal biodiversity of bathyal habitats at the moroccan carbonate province (Gulf of Cadiz, NE atlantic) - Casais, Joana Filipa Monteiro (2018)
The Gulf of Cadiz is an extensive seepage area between the south Iberian and north Moroccan margins, west of the Strait of Gibraltar (NE Atlantic). It encompasses numerous carbonate mounds characterised by accumulations of mostly fossil deepwater corals, isolated coral patches and coral rubble, and over 40 submarine mud volcanoes at depths ranging 200 to 4,000m. This tectonically active area has a long geologic history and a central biogeographic location. The complex circulation of water masses ensures oceanographic connectivity with the Mediterranean Sea, Equatorial and North Atlantic regions. At the Gulf of Cadiz, the Pen Duick Escarpment, a feature with 4 km length and 100 m height, is located at ca. 500 m depth, on the south-eastern branch of the Renard Ridge, westwards of the El Arraiche mud volcano field. Cold-water corals, vulnerable, slow-growing metazoans that inhabit cold dark waters in the deep-sea, have been receiving increased attention in recent years. Under the framework of the research programs MiCROSYSTEMS and Moundforce (European Science Foundation), selected sites along the Moroccan margin were investigated, aiming to describe the composition, abundance and community structure of the benthic macrofaunal assemblages living in association with fossil cold-water coral reef habitats present in the vicinity of mud volcanoes and carbonate mounds. Sampling was undertaken during the cruises M2005 (64PE237), M2006 (64PE253) and M2007 (64PE268), onboard the RV Pelagia. From the 120 box-core subsamples collected at depths ranging 220 to 900 m, 426 macroinvertebrate taxa were identified. The macrofaunal assemblages were highly heterogeneous in composition and community structure and were mainly represented by arthropods, annelids and molluscs. Multivariate analyses supported significant differences between distinct geological features and between distinct substrate types. High diversity, abundance and evenness were common in mound, coral and mud volcano assemblages, whilst off mound sediments and areas without hard substrates were represented by less diverse and less abundant assemblages. The assemblages are dominated by a relatively low percentage of the most common taxa and include mainly polychaetes, sipunculids and tanaidaceans. Analysis in relation to depth also revealed differences in taxa richness and abundance. The results obtained are discussed in relation to previous knowledge on carbonate mounds, fossil coral reefs, El Arraiche mud volcanoes and surrounding area, reinforcing the hypothesis that the presence of carbonate mounds and fossil cold-water coral reefs increases deep-sea habitat heterogeneity and support a highly diverse assemblage of benthic invertebrates.